Clinicopathological characteristics of breast cancer patients with NOD2 mutation according to age - Huszno, Joanna (Contemp Oncol (Pozn), 2020)
INTRODUCTION: The purpose of the present study was to characterise patients with breast cancer (BC) and NOD2-mutation (age ≥ 50 years) according to their clinicopathological factors or family history. Patients aged ≥ 50 years were compared with the control group and with NOD2-mutation carriers aged < 50 years. MATERIAL AND METHODS: Prognostic factors were analysed in patients with BC with confirmed NOD2 c.3016_3017insC (n = 150) mutations. The control group was selected from patients with BC without mutations (n = 376). RESULTS: There were significant differences between NOD2-mutation carriers and the control group aged ≥ 50 years, according to HER2 overexpression (p = 0.0001), ER (–) (p = 0.007), PR (–) (p = 0.003), T1–T2 (p = 0.011), and G3 (p = 0.036). Similarly, significant differences were observed between NOD2-mutation carriers and the control group aged < 50 years, according to HER2 overexpression (p = 0.0001), ER (–) (p = 0.049), and N (+) (p = 0.038). In patients aged ≥ 50 years, family history of cancer, including BC, was observed more often in NOD2-mutation carriers compared with the control group of patients (OR = 1.66; p = 0.072, for BC in family history: OR = 2.65; p = 0.002). NOD2-mutation carriers aged ≥ 50 years had significantly less frequent G3 (p = 0.004) and HER2 overexpression (p = 0.043) compared with patients with NOD2 mutation aged < 50 years. CONCLUSIONS: The presence of the NOD2 mutation is not only characteristic of younger patients but also in patients > 50 years of age. In NOD2-mutation carriers aged ≥ 50 years, the presence of larger tumour size, G3, or HER2 overexpression were lower compared with younger patients with NOD2 mutation.